Development of Therapeutic RNA Manipulation for Muscular Dystrophy - Saifullah,; Motohashi, Norio; Tsukahara, Toshifumi; Aoki, Yoshitsugu (Frontiers in Genome Editing, 2022)
Approval of therapeutic RNA molecules, including RNA vaccines, has paved the way for next-generation treatment strategies for various diseases. Oligonucleotide-based therapeutics hold particular promise for treating incurable muscular dystrophies, including Duchenne muscular dystrophy (DMD). DMD is a severe monogenic disease triggered by deletions, duplications, or point mutations in the DMD gene, which encodes a membrane-linked cytoskeletal protein to protect muscle fibers from contraction-induced injury. Patients with DMD inevitably succumb to muscle degeneration and atrophy early in life, leading to premature death from cardiac and respiratory failure. Thus far, the disease has thwarted all curative strategies. Transcriptomic manipulation, employing exon skipping using antisense oligonucleotides (ASO) has made significant progress in the search for DMD therapeutants. Several exon-skipping drugs employing RNA manipulation technology have been approved by regulatory agencies and have shown promise in clinical trials. This review summarizes recent scientific and clinical progress of ASO and other novel RNA manipulations, including RNA-based editing using MS2 coat protein-conjugated adenosine deaminase acting on the RNA (MCP-ADAR) system, illustrating the efficacy and limitations of therapies to restore dystrophin. Perhaps lessons from this review will encourage application of RNA-editing therapy to other neuromuscular disorders.